The person-based approach to intervention development: A scoping review of methods and applications - Lydia Holt; Sarah Denford; Hannah Bowers; Paula Kuberka; Ingrid Muller; Richard Amlôt; Lucy Yardley (Digital Health)
Background The person-based approach (PBA) has emerged as a prominent methodology guiding the development of digital and hybrid health behaviour change interventions over the last decade, and there is a salient need to understand its utilization. Objective This study aims to describe which elements of the PBA have been utilised in intervention development research, for which populations, and how this has been reported. Methods A search for intervention development papers published between 2015 and 2023 using forward citation searches was undertaken in Scopus, using two seed articles. Results are presented using frequency counts, and qualitative data were summarised using content analysis. Results The review encompasses 239 papers. The PBA has frequently been applied in early stage development of digital interventions for adult populations, prioritising the use of qualitative methods. It has been used globally to develop, adapt, optimise and evaluate digital, hybrid and offline interventions for a wide range of contexts including primary and secondary healthcare, educational, community, and public health settings. Researchers value it as a proven method to identify user needs and preferences in order to create persuasive content. Conclusion The PBA is most frequently linked to research undertaken to understand target populations and iteratively design content in early development phases. The PBA provides guidance on combining evidence-, theory- and person-based research, but these three elements are not always evident in the literature. Training focused on these elements, plus exemplar studies and use of reporting guidelines, could make this integrative work more visible in future papers.